Antibody-removal therapies for de novo DSA in pediatric intestinal recipients: Why, when, and how? A single-center experience - María Lasa-Lázaro; Esther Ramos-Boluda; Esther Mancebo; María José Castro-Panete; Rocío González-Sacristán; Javier Serradilla; Javier Serradilla; Ane Miren Andrés-Moreno; Ane Miren Andrés-Moreno; Francisco Hernández-Oliveros; Francisco Hernández-Oliveros; Estela Paz-Artal; et al. (Frontiers Media S.A., 2023)
BackgroundDonor-specific anti-HLA antibodies (DSA) impact negatively on the outcome of intestinal grafts. Although the use of antibody-removal therapies (ART) is becoming more frequent in the last few years, issues regarding their timing and effectiveness remain under discussion.MethodsIn the present study, we report our experience with eight ART procedures (based on plasmapheresis, intravenous immunoglobulin, and rituximab) in eight pediatric intestinal and multivisceral transplants with de novo DSA (dnDSA).ResultsART were performed when dnDSA appeared in two contexts: (1) concomitant with rejection (acute or chronic) or (2) without rejection or any other clinical symptom. Complete DSA removal was observed in seven out of eight patients, showing an effectiveness of 88%. In the group treated for dnDSA without clinical symptoms, the success rate was 100%, with complete DSA removal and without rejection afterward. A shorter time between DSA detection and ART performance appeared as a significant factor for the success of the therapy (p = 0.0002). DSA against HLA-A and DQ alleles were the most resistant to ART, whereas anti-DR DSA were the most sensitive. In addition, the 8-year allograft survival rate in recipients undergoing ART was similar to that in those without DSA, being significantly lower in non-treated DSA-positive recipients (p = 0.013).ConclusionThe results confirm the effectiveness of ART in terms of DSA removal and allograft survival and encourage its early use even in the absence of clinical symptoms.